Molecular characterization of Blastocrithidia culicis L17 ribosomal protein - Manzine, Livia Regina; Alves da Silva, Marco Tulio; Thiemann, Otavio Henrique; Cicarelli, Regina Maria Barretto [UNESP] (Nencki Inst Experimental Biology, 2006)
Blastocrithidia culicis is a protozoan of the family Trypanosomatidae. It is a parasite of insects, but the presence of bacteriumlike endosymbionts in its cytoplasm led some investigators to study this protozoan. This trypanosomatid does not infect humans and although it is phylogenetically distant from Trypanosoma cruzi, it presents many morphological characteristics, which are similar. In previous studies our group showed the presence of a L27 ribosomal protein in T cruzi (named TcrL27) using a RT-PCR, which also resulted in the cloning, sequencing and expression of an unexpected ribosomal protein, L17, in Blastocrithidia culicis (BcL17). In this paper, Western blot analysis demonstrated that the anti-BcL17 antibody recognizes the presence of the same ribosomal protein either in Blastochritidia culicis and T. cruzi nuclear extracts. Besides, two similar bands (40 and 47 kDa) appeared also in T. cruzi isolated ribosomal proteins and B. culicis nuclear extract corroborating with the findings showed in the phylogenetic reconstruction. With respect to their localization within the ribosome, both the L17 and L27 ribosomal proteins appear to belong to the peptidyl-transferase site, and are therefore part of the key step in protein synthesis. Both ribosomal proteins bind spiramycin derivatives, being therefore compounds of the macrolides connection sites in the ribosome. These findings would open a possibility to better evaluate this issue.
Keywords: Blastocrithidia culicis; L17 ribosomal protein; recombinant ribosomal protein; trypanosomatids